2022
DOI: 10.3389/fsurg.2022.917172
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil-to-lymphocyte ratio: A potential predictor of poor prognosis in adult patients with trauma and traumatic brain injury

Abstract: PurposeThis study aimed to determine the prognostic impact of the neutrophil-to-lymphocyte ratio (NLR) in critically ill trauma patients.MethodsThis retrospective study involved adult trauma patients from 335 intensive care units (ICUs) at 208 hospitals stored in the eICU database. The primary outcome was ICU mortality. The lengths of ICU and hospital stay were calculated as the secondary outcomes. The multivariable logistic regression model was used to identify independent predictors of mortality. To identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…[17] Xu et al mentioned that an NLR > 7.44 was an independent risk factor for intensive care unit death in patients with TBI. [18] Similarly, we observed that NLR > 6.15 was associated with unfavorable outcome (both 30-day mortality and 90-day recovery) of PBH. Physiologically, the NLR represents the balance between the inflammatory activator and inflammatory regulator.…”
Section: Discussionsupporting
confidence: 62%
“…[17] Xu et al mentioned that an NLR > 7.44 was an independent risk factor for intensive care unit death in patients with TBI. [18] Similarly, we observed that NLR > 6.15 was associated with unfavorable outcome (both 30-day mortality and 90-day recovery) of PBH. Physiologically, the NLR represents the balance between the inflammatory activator and inflammatory regulator.…”
Section: Discussionsupporting
confidence: 62%
“…[11][12][13][14][15][16][17][18][19] One study associated a high NLR with a poor prognosis in trauma patients, particularly those with traumatic brain injury. [25] High NLR and PLR have also been linked to poor outcomes in various diseases. According to our study's results, high NLR and PLR are associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%